Low occurrence of equine herpesvirus 1 (EHV-1) as cause of abortion and perinatal mortality in Brazil - Silva, Aline Aparecida da (2018)
Equine herpesvirus type 1 (EHV-1) is an important pathogen that causes abortion, neonatal disease, respiratory disorders, and neurological syndrome in equine populations worldwide. To evaluate EHV-1 as a cause of abortion and perinatal mortality in Brazil, tissue samples from 105 aborted equine fetuses, stillbirths, and foals up to one month of age were examined using virus isolation, immunohistochemistry (IHC), histopathology, and nested polymerase chain reaction (PCR). Two fetuses were positive for EHV-1 by PCR, one of which showed syncytia and eosinophilic intranuclear inclusion bodies in bronchial epithelia, but it was negative by virus isolation. The other showed no characteristic histological lesions, but it was positive by viral isolation. No sample was positive by IHC. The results presented low occurrence of EHV-1 in the studied population and suggested that the use of a combination of techniques increases the likelihood of an accurate diagnosis of EHV-1.